The Influence of Green Investment and Media Exposure on Carbon Emission Disclosure (Case Study on Oil, Gas and Coal Energy Subsector Companies Listed on the Indonesia Stock Exchange in 2021-2023) - Citra, Yulia; Sastradipraja, Usman (DINASTI RESEARCH, 2025)
Climate change is an increasingly urgent environmental issue, driven by global warming due to rising carbon emissions and greenhouse gases. This study aims to explore the impact of green investment and media exposure on carbon emissions disclosure by companies. This research uses a quantitative approach that relies on data collection through literature review and documentation. The focus of the study is on companies in the oil, gas, and coal subsector listed on the Indonesia Stock Exchange during the period of 2021-2023. A purposive sampling method was used, involving 28 companies over a period of 3 years, resulting in 84 observation data points. Data analysis was conducted using classical assumption tests, multiple linear regression, autocorrelation tests, coefficient of determination, t-tests, and f-tests, processed with IBM SPSS version 25. The findings reveal that green investment does not have a significant effect on carbon emissions disclosure. In contrast, media exposure has a negative impact, where greater media attention to the issue correlates with a lower tendency for companies to disclose carbon emissions transparently. These findings emphasize the need for policies that support transparency in carbon emissions disclosure, as well as more effective communication strategies to encourage companies to be more transparent about their carbon emissions.